What a poor illiterate man saw in Florida - Paddock
Manuscript travel journal kept by Paddock (given name unknown) while traveling from New York to Florida during Reconstruction. Describes the vote in Congress to readmit the state of Virginia to the Union. Also includes a typewritten transcript of a portion of the journal.
Typewritten transcript, in part.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Congress; Reconstruction (U.S. history, 1865-1877); Reconstruction (U.S. history, 1865-1877) -- Virginia; Atlantic Coast (U.S.) -- Description and travel; Florida -- Description and travel; New York (State) -- Description and travel; Virginia -- History -- 1865-1950.